2007
DOI: 10.1007/s11064-007-9469-8
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the Mechanism of Alzheimer’s Disease Aβ Peptide Neurotoxicity

Abstract: The Alzheimer's disease neurotoxic amyloid-beta (A beta) peptide is derived from the larger amyloid precursor protein (APP) and is the principal component of the senile plaques in Alzheimer's disease (AD) brains. This mechanism by which A beta mediates neurotoxicity or neuronal dysfunction is not fully resolved. This review will outline some of the key determinants that modulate A beta's activity and the cellular pathways and mechanisms involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 106 publications
1
77
0
Order By: Relevance
“…The amyloid hypothesis has undergone several modifications, mainly concerning the type of A␤ thought to cause AD: initially this was the amyloid plaque, followed by increased concentrations of A␤ 42 , then increased A␤ 42 : A␤ 40 ratio, and finally oligomeric A␤ [2]. Results from clinical trials have shown that removing plaques will not reverse the damage or stop AD [3,4]. Recent evidence suggests that this toxicity may be linked to the aggregation state of the peptide, implicating oligomers, rather than insoluble fibrils, as the primary toxic species [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The amyloid hypothesis has undergone several modifications, mainly concerning the type of A␤ thought to cause AD: initially this was the amyloid plaque, followed by increased concentrations of A␤ 42 , then increased A␤ 42 : A␤ 40 ratio, and finally oligomeric A␤ [2]. Results from clinical trials have shown that removing plaques will not reverse the damage or stop AD [3,4]. Recent evidence suggests that this toxicity may be linked to the aggregation state of the peptide, implicating oligomers, rather than insoluble fibrils, as the primary toxic species [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The various experimental studies reported the role of rich feeding from anti-inflammations and anti-oxidants in recovery of neuro toxicity and recovery of the act of the brain (Cappai and et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This was the case despite Y10A mutant producing H 2 O 2 at half the rate of that by the wild-type peptide. Cappai and Barnham (2008) proposed that the covalently cross-linked oligomers produced by this Cu(II) catalyzed redox process is the genesis of -induced neurotoxicity. Hence, it is possible that the Cu(II)/redox chemistry initiates the generation of toxic soluble oligomers (which are toxic by mechanisms as of yet undetermined) rather than the neurodegeneration in AD being directly the result of the ROS generation.…”
Section: Copper and Amyloid Betamentioning
confidence: 99%